Congenital hypodontia: a pedigree and dermatoglyphic study - (:unkn) unknown (My University, 1995)
The dermatoglyphs and the pedigrees of 11 male and 10 female, a total of 21 patients with congenital hypodontia (CH) were investigated. The dermatoglyphics of the patients were compared with those of 250 male and 250 female control cases. There were more arches on the finger-tips of the patients with absence of the lateral incisors, absence of the second premolars and a total patients with CH. The patients with absence of the lateral incisors had more palmar ll and plantar lll loops and p triradii. The patients with absence of the second premolars had more H and H loops, P triradii and plantar ll loops. A total patients with CH had more palmar ll and plantar lll, IV loops and p and z triradii. The pedigrees of the patients with both absence of the lateral incisors and the second premolars showed that the inheritance patterns of both conditions would seem autosomal recessive.
Keywords: Female; Humans; Turkey; Adolescent; Male; Child; Anodontia; Case-Control Studies; Pedigree; Dermatoglyphics; Genes, Recessive